2019
DOI: 10.1038/s41598-019-42935-y
|View full text |Cite
|
Sign up to set email alerts
|

Binding studies of a putative C. pseudotuberculosis target protein from Vitamin B12 Metabolism

Abstract: Vitamin B 12 acts as a cofactor for various metabolic reactions important in living organisms. The Vitamin B 12 biosynthesis is restricted to prokaryotes, which means, all eukaryotic organisms must acquire this molecule through diet. This study presents the investigation of Vitamin B 12 metabolism and the characterization of precorrin-4 C(11)-methyltransferase (CobM), an enzyme involved in the biosynthesis of Vitamin B 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…In this study, we observed that Unidentified Corynebacteriaceae was positively correlated with Vitamin B12 concentrations. It has been reported that Corynebacterium could synthesize Vitamin B12 through the characterization of precorrin‐4 C(11)‐methyltransferase (CobM), an enzyme involved in the biosynthesis of Vitamin B12 (Peinado et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that Unidentified Corynebacteriaceae was positively correlated with Vitamin B12 concentrations. It has been reported that Corynebacterium could synthesize Vitamin B12 through the characterization of precorrin‐4 C(11)‐methyltransferase (CobM), an enzyme involved in the biosynthesis of Vitamin B12 (Peinado et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While decades-old literature have implicated Corynebacterium species in de novo cobamide biosynthesis [55][56][57], only a few recent studies have explored this relatively rare function by members of the genus [31,[58][59][60]. Here, we demonstrate that within the Corynebacterium genus, the de novo cobamide biosynthesis pathway is conserved among specific lineages, including those that contain skin-associated species (Figure 3).…”
Section: Retention Of the Energetically Costly 25-enzyme Cobamide Biomentioning
confidence: 61%
“…It has been reported that the nutrition provided by vitamins promotes growth and immune function in developing calves [ 66 ] and that vitamins are responsible for the development of the organism, immunity, and the maintenance, regulation, and repair of tissues through their various metabolites [ 67 ]. In addition, vitamins are cofactors for different critical metabolic reactions in organisms [ 68 ].…”
Section: Discussionmentioning
confidence: 99%